2011
DOI: 10.5851/kosfa.2011.31.1.032
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Lotus Leaf (Nelumbo nucifera) Powder and Barley Leaf (Hordeum vulgare) Powder in Raw Minced Pork during Chilled Storage

Abstract: The effects of additions of lotus leaf (0.1 and 0.5%) and barley leaf powder (0.1 and 0.5%) on the lipid oxidation and microbiological analysis of raw minced pork were investigated after 1, 4, 7, and 10 d at chilled storage. Days of storage caused (p<0.05) decreases in pH values in samples with lotus leaf (LP) and barley leaf powder (BP). L* and a* values decreased, and b* values increased in the treatments with increasing lotus leaf and barley leaf powder contents, respectively. The decrease in a * values was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Several studies have shown that synthetic or natural preservatives could be used to control microbial spoilage and lipid oxidation (Jayasena & Jo 2013;Karre et al 2013;Falowo et al 2014). The level of interest that has been shown in natural antioxidants in meat products at utilization has increased significantly, especially since consumers became concerned about the use of synthetic antioxidants, due to their potential toxicological effects (Choe et al 2011;Karre et al 2013;Falowo et al 2014). Several plant sources have shown natural antimicrobial and antioxidant properties, and different kinds of vegetables, fruits, aromatic plants and spices could be used for this purpose (Hygreeva et al 2014).…”
mentioning
confidence: 99%
“…Several studies have shown that synthetic or natural preservatives could be used to control microbial spoilage and lipid oxidation (Jayasena & Jo 2013;Karre et al 2013;Falowo et al 2014). The level of interest that has been shown in natural antioxidants in meat products at utilization has increased significantly, especially since consumers became concerned about the use of synthetic antioxidants, due to their potential toxicological effects (Choe et al 2011;Karre et al 2013;Falowo et al 2014). Several plant sources have shown natural antimicrobial and antioxidant properties, and different kinds of vegetables, fruits, aromatic plants and spices could be used for this purpose (Hygreeva et al 2014).…”
mentioning
confidence: 99%
“…The addition of non-meat ingredients in meat products could induce undesirable change in color, depending on its intrinsic color and addition level [19, 20]. In this study, the addition of the powders (GTL, LL, and KC) to sausage samples significantly influenced the change in color (Table 1).…”
Section: Resultsmentioning
confidence: 80%
“…Lipid oxidation is commonly determined by measuring thiobarbituric acid reactive substances (TBARS), which are secondary lipid reaction products including aldehydes, carbonyls, and hydrocarbons [19]. In this study, TBARS values of sausage samples ranged from 0.17 to 0.28 mg MDA/kg meat during two weeks of storage (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Barley leaves extracted by methanol and ethanol may be alternatives to synthetic antioxidants in the food industry [ 114 ]. Barley leaf powder can be incorporated into raw minced pork as natural additives to retard oxidation [ 116 ]. Feeds supplemented with barley leaves containing antioxidants enhanced pork quality by increasing the levels of unsaturated oleic and gondoic acids [ 117 ].…”
Section: Preventive Chronic Disease Of Barley Grassmentioning
confidence: 99%